2020
DOI: 10.1002/eji.202049058
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence but short‐lived immune response to SARS‐CoV‐2 infection in Paris

Abstract: Although the COVID‐19 pandemic peaked in March/April 2020 in France, the prevalence of infection is barely known. Using high‐throughput methods, we assessed herein the serological response against the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) of 1847 participants working in three sites of an institution in Paris conurbation. In May–July 2020, 11% (95% confidence interval [CI]: 9.7–12.6) of serums were positive for IgG against the SARS‐CoV‐2 N and S proteins, and 9.5% (95% CI: 8.2–11.0) were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 49 publications
(73 reference statements)
6
53
0
Order By: Relevance
“…This was also observed in Importantly, seroconversion of IgG against SARS-CoV-2 from positive to negative or weak positive occurred 53.4% in asymptomatic carriers and 25.5% in COVID-19 patients ( P =0.059), while consistently seropositive rate of IgG against SARS-CoV-2 was significantly higher in COVID-19 patients than in asymptomatic carriers ( P =0.037). The similar observations concerning rapid seroconversion of the antibody against SARS-CoV-2 or short-lived immune response after mild infection were also reported in the frontline health care personnel in the US and active workers in France [23, 24]. These data indicate that humoral immunity against SARS-CoV-2 was not efficiently aroused by a relative short exposure of SARS-CoV-2 in asymptomatic carriers or in those with a stronger innate and cell immunity.…”
Section: Discussionsupporting
confidence: 77%
“…This was also observed in Importantly, seroconversion of IgG against SARS-CoV-2 from positive to negative or weak positive occurred 53.4% in asymptomatic carriers and 25.5% in COVID-19 patients ( P =0.059), while consistently seropositive rate of IgG against SARS-CoV-2 was significantly higher in COVID-19 patients than in asymptomatic carriers ( P =0.037). The similar observations concerning rapid seroconversion of the antibody against SARS-CoV-2 or short-lived immune response after mild infection were also reported in the frontline health care personnel in the US and active workers in France [23, 24]. These data indicate that humoral immunity against SARS-CoV-2 was not efficiently aroused by a relative short exposure of SARS-CoV-2 in asymptomatic carriers or in those with a stronger innate and cell immunity.…”
Section: Discussionsupporting
confidence: 77%
“…Importantly, seroconversion of IgG against SARS-CoV-2 from positive to negative or weak positive occurred 53.4% in asymptomatic carriers and 25.5% in COVID-19 patients (P = 0.059), while consistently seropositive rate of IgG against SARS-CoV-2 was signi cantly higher in COVID-19 patients than in asymptomatic carriers (P = 0.037). The similar observations concerning rapid seroconversion of the antibody against SARS-CoV-2 or short-lived immune response after mild infection were also reported in the frontline health care personnel in the US and active workers in France [22,23]. These data indicate that humoral immunity against SARS-CoV-2 was not e ciently aroused by a relative short exposure of SARS-CoV-2 in asymptomatic carriers or in those with a stronger innate and cell immunity.…”
Section: Discussionsupporting
confidence: 79%
“…Several studies similarly reported that only a fraction of seropositive individuals had detectable levels of neutralising antibodies, this fraction being variable 2 , 3 , 7 – 9 . This finding could be explained by differences in antibody kinetics with delayed appearance of neutralising antibodies 20 .…”
Section: Discussionmentioning
confidence: 99%